TRANSFORMING EGA SARI MSME INTO A SUSTAINABLE BUSINESS THROUGH BOOKKEEPING DIGITALIZATION, PRODUCT INNOVATION, AND DIGITAL MARKETING STRATEGY MENTORSHIP - Efrianti, Desi; Sutarti, Sutarti; Sukamto, Anton; Rohmah, Siti; Meishanda Putri Komara Mukti, Nikita (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in strengthening Indonesia’s economy, as nearly 99% of all business entities originate from this sector. In terms of contribution, MSMEs account for 60.5% of the Gross Domestic Product (GDP) and provide 96.9% of employment opportunities nationwide. Despite their significant role, this sector continues to face challenges in business management. Similar conditions are experienced by Ega Sari Home Industry, which encounters three key issues: organizational governance, resource management, and marketing strategy. To address these challenges, the IBIK Community Service Team designed several solution programs, including: 1) training and mentoring in the formulation of organizational management policies, 2) simulation and guidance in preparing financial reports using Excel, 3) entrepreneurship training and marketing strategy development, and 4) marketing assistance through technology-based practices such as product label design, packaging improvement, and social media optimization. These programs were implemented through a community service method that involved mentoring from production processes to marketing assistance. This initiative is expected to raise MSME awareness in product innovation, packaging, and digital marketing, thereby enhancing competitiveness.